Peningkatan Pemahaman Konsep Bilangan Cacah Pada Operasi Perkalian Dengan Menggunakan Model Contextual Teaching And Learning (CTL) : penelitian tindakan kelas dengan menggunakan model Contextual Teaching And Learning di kelas III SDN 1 Sukamanah - Fitria Ainawati; Rizki Hadiwijaya Zulkarnaen; Deni Chandra (STKIP Subang, 2025)
This study aims to improve students' understanding of concepts through the application of the Contextual Teaching and Learning (CTL) model in mathematics learning, specifically in the material of multiplication of whole numbers. The research method used is classroom action research (CAR) which consists of planning, action, observation, and reflection in each cycle. The subjects of this study are third-grade students of SDN 1 Sukamanah, totaling 23 students, consisting of 10 female students and 13 male students. Data collection methods include observation, evaluation sheets, LKPD (student worksheets), and documentation. Based on the analysis of data in cycle I, the average understanding of students' concepts is 65.22%, which falls into the moderate category, and in cycle II, the average understanding of students' concepts is 91.30%, which falls into the very good category. From the results of the study, it can be concluded that the application of the Contextual Teaching and Learning (CTL) model can improve students' understanding of concepts in the material of multiplication of whole numbers.